Widespread brain distribution and activity following i.c.v. infusion of anti‐β‐secretase (BACE1) in nonhuman primates. (6th October 2017) - Yadav, Daniela Bumbaca; Maloney, Janice A; Wildsmith, Kristin R; Fuji, Reina N; Meilandt, William J; Solanoy, Hilda; Lu, Yanmei; Peng, Kun; Wilson, Blair; Chan, Pamela; Gadkar, Kapil; Kosky, Andrew; et al.
Abstract : Background and Purpose: The potential for therapeutic antibody treatment of neurological diseases is limited by poor penetration across the blood–brain barrier. I.c.v. delivery is a promising route to the brain; however, it is unclear how efficiently antibodies delivered i.c.v. penetrate the cerebrospinal spinal fluid (CSF)‐brain barrier and distribute throughout the brain parenchyma. Experimental Approach: We evaluated the pharmacokinetics and pharmacodynamics of an inhibitory monoclonal antibody against β‐secretase 1 (anti‐BACE1) following continuous infusion into the left lateral ventricle of healthy adult cynomolgus monkeys. Key Results: Animals infused with anti‐BACE1 i.c.v. showed a robust and sustained reduction (~70%) of CSF amyloid‐β (Aβ) peptides. Antibody distribution was near uniform across the brain parenchyma, ranging from 20 to 40 nM, resulting in a ~50% reduction of Aβ in the cortical parenchyma. In contrast, animals administered anti‐BACE1 i.v. showed no significant change in CSF or cortical Aβ levels and had a low (~0.6 nM) antibody concentration in the brain. Conclusion and Implications: I.c.v. administration of anti‐BACE1 resulted in enhanced BACE1 target engagement and inhibition, with a corresponding dramatic reduction in CNS Aβ concentrations, due to enhanced brain exposure to antibody.